2011
DOI: 10.1258/ar.2010.100239
|View full text |Cite
|
Sign up to set email alerts
|

Imaging findings and accuracy of core needle biopsy in mucinous carcinoma of the breast

Abstract: CNB was found to be a highly reliable diagnostic tool for diagnosing mucinous carcinoma in this selected material. US findings of pure mucinous carcinoma were variable, however, all reached BI-RADS 4 category. The presence of posterior acoustic enhancement beneath a solid breast lesion should raise suspicion of mucinous carcinoma. Most of the tumors appeared as BI-RADS 4 lesions in US and in mammography thus making both a useful tool for raising a suspicion of malignancy in mucinous cancers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(18 citation statements)
references
References 21 publications
0
17
1
Order By: Relevance
“…PMBC are commonly lobulated; 6,9,14,15 however, the lesions in our series often demonstrated additional mammographic features that raise the suspicion for malig-nancy. This Australian study is the largest contiguous series of screen-detected PMBC in an asymptomatic population to date.…”
Section: Discussionmentioning
confidence: 63%
See 4 more Smart Citations
“…PMBC are commonly lobulated; 6,9,14,15 however, the lesions in our series often demonstrated additional mammographic features that raise the suspicion for malig-nancy. This Australian study is the largest contiguous series of screen-detected PMBC in an asymptomatic population to date.…”
Section: Discussionmentioning
confidence: 63%
“…PMBC are commonly lobulated; 6,9,14,15 however, the lesions in our series often demonstrated additional mammographic features that raise the suspicion for malig-nancy. 6,14 Although 25% of tumours in this study could be identified retrospectively on an earlier mammogram, which is lower than the 38% described by Dhillon et al, 16 delay in diagnosis did not affect prognosis, with no significant differences in tumour size (12.5 mm compared with 15 mm) or axillary nodal metastasis (5% compared with 9%). None of the lesions in this large series presented mammographically with completely smooth, sharply defined margins typical of a simple breast cyst.…”
Section: Discussionmentioning
confidence: 63%
See 3 more Smart Citations